Green NP‐HPTLC and green RP‐HPTLC methods for the determination of thymoquinone: A contrast of validation parameters and greenness assessment. Issue 2 (5th July 2021) - Foudah, Ahmed I.; Shakeel, Faiyaz; Alqarni, Mohammed H.; Ross, Samir A.; Salkini, Mohammad A.; Alam, Prawez
Abstract: Introduction: Thymoquinone (TQ) is a naturally derived bioactive compound with several therapeutic effects. Objective: The highly sensitive, rapid and green normal‐phase (NP)/reversed‐phase (RP) high‐performance thin‐layer chromatography (HPTLC) densitometry technique was developed for the determination of TQ in various plant extracts of different geographical regions, commercial capsules, creams and essential oils. Methodology: The NP densitometry estimation of TQ was performed using a cyclohexane–ethyl acetate (90:10, v/v ) green solvent system, while, the RP‐densitometry estimation of TQ was performed using an ethanol–water (80:20, v/v ) green solvent system. The estimation of TQ was conducted at 259 nm. Results: The NP and RP densitometry techniques were observed linear in the range of 25–1000 and 50–600 ng/band, respectively. All validation parameters such as accuracy, precision, robustness and sensitivity of NP/RP densitometry were observed within the limit of regulatory requirements and hence found to be suitable for the determination of TQ. The TQ contents were found to be highest in the Saudi Arabian extract followed by the Syrian extract, Indian extract, commercial capsules, commercial creams, Jordanian extract, Egyptian extract, Palestinian extract and commercial essential oils using NP densitometry. The TQ contents were found in same order using RP densitometry, but they were much lower than those recorded using NP densitometry. The Analytical GREEnness (AGREE) scores of NP and RP densitometry were found to be 0.82 and 0.84, respectively, suggesting an excellent greenness profile. Conclusions: Based on these results, NP/RP densitometry was found to be suitable for the pharmaceutical assay of TQ. Abstract : The NP and RP densitometry techniques were observed linear. The TQ contents were found to be highest in the Saudi Arabian extract sing NP/RP densitometry. The AGREE scores of the NP and RP densitometry were found to be 0.82 and 0.84, respectively.